DEVELOPMENT OF INTERACTIVE MULTIMEDIA LEARNING USING ARTICULATE STORYLINE ON LAN CABLE CRIMPING MATERIAL AT NU TULUNGAGUNG VOCATIONAL SCHOOL - Sela Nofitasari; Anggara Sukma Ardiyanta; Heri Suhendar (STKIP PGRI TULUNGAGUNG, 2024)
In class and passive. In this case, it is necessary to develop interesting learning media to increase students' interest in learning. The aim of this research is to develop interactive learning multimedia using Articulate Storyline on appropriate LAN cable crimping material at SMK NU Tulungagung. This interactive learning media was created through a research and development (RD) approach using Articulate Storyline. The development research model used is the ADDIE model (Analysis, Design, Development, Implement and Evaluation). This development research uses qualitative and quantitative descriptive analysis. The research subjects included media experts, namely lecturers at Bhinneka PGRI University, material experts, namely teachers of Basic Computer Network Engineering and Telecommunications subjects and class X TKJ students at SMK NU Tulungagung as respondents. The instruments used to assess product suitability include media expert validation, material expert validation and user assessment. The results of the media expert trial produced a feasibility percentage of 91.6%, which indicates a very feasible feasibility level. Likewise, the material expert trial resulted in a feasibility percentage of 95%, which indicates a very feasible feasibility level. In a small group experiment, it resulted in a feasibility percentage of 94.16% which indicated a very feasible feasibility level. In a large group experiment, it resulted in a feasibility percentage of 91.52% which indicated a very feasible feasibility level. Therefore, the interactive learning multimedia developed by researchers, using Articulate Storyline on LAN cable crimping material, is very suitable to support the teaching and learning activities of class X TKJ students at SMK NU Tulungagung.